2013
DOI: 10.1007/s12010-013-0229-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Fructosamine-6-Kinase from Arthrobacter aurescens

Abstract: Fructosamine-6-kinases (FN6Ks) that catalyze phosphorylation of glycated amino acids, i.e., fructosyl amino acids (FAs), have been shown as a potential recognition element for glycated protein detection. However, there are only two available FN6Ks: those from Escherichia coli which is specific for ε-fructosyl lysine (ε-FK) and Bacillus subtilis which recognizes both ε-FK and α-FA as substrates. In this study, we characterized an FN6K homologue isolated from Arthrobacter, some of whose species are reported to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…FN6Ks have been identified in Escherichia coli, Bacillus subtilis, and Arthrobacter aurescens. [22][23][24] In these bacteria, FN6K catalyzes the production of fructosamine 6-phosphate by phosphorylating fructosamine at the C6 of the deoxyfructose moiety. Following phosphorylation, deglycase catalyzes the degradation of fructosamine 6-phosphate to free amino acid and glucose 6-phosphate ( Figure 1C).…”
Section: Property Of Fructosamine 3-kinase and Fructosamine 6-kinasementioning
confidence: 99%
See 2 more Smart Citations
“…FN6Ks have been identified in Escherichia coli, Bacillus subtilis, and Arthrobacter aurescens. [22][23][24] In these bacteria, FN6K catalyzes the production of fructosamine 6-phosphate by phosphorylating fructosamine at the C6 of the deoxyfructose moiety. Following phosphorylation, deglycase catalyzes the degradation of fructosamine 6-phosphate to free amino acid and glucose 6-phosphate ( Figure 1C).…”
Section: Property Of Fructosamine 3-kinase and Fructosamine 6-kinasementioning
confidence: 99%
“…22,36 The substrate specificity of the B. subtilis FN6K differs from those of the E. coli and A. aurescens FN6Ks, although they share 50% similarity in amino acid sequences. 24 The FN6K from B. subtilis shows broader substrate specificity, catalyzing the phosphorylation of both ε-FK and α-glycated amino acids, such as fructosyl valine. In contrast, the FN6Ks from E. coli and A. aurescens preferentially catalyze the phosphorylation of ε-FK (Table 1).…”
Section: Property Of Fructosamine 3-kinase and Fructosamine 6-kinasementioning
confidence: 99%
See 1 more Smart Citation
“…FN6K catalyzes the production of fructosamine 6‐phosphate by phosphorylating fructosamine at C6 of the deoxyfructose moiety, which is followed by the degradation of fructosamine 6‐phosphate to the free amino acid and glucose 6‐phosphate, catalyzed by deglycase . FN6Ks have been identified in Escherichia coli and Bacillus subtilis , and our group has reported the FN6K from Arthrobacter aurescens . The FN6Ks from E. coli and A. aurescens preferentially catalyze the phosphorylation of ε‐fructosyl lysine (ε‐FK), while the FN6K from B. subtilis shows broader substrate specificity against both ε‐FK and α‐glycated amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the enzymatic activity of FN6Ks for ε‐FK can be measured colorimetrically by coupling with pyruvate kinase, pyruvate oxidase, and peroxidase reactions and detecting quinoneimine dye, as shown in Fig. . The application of this sensing scheme for the detection of GA is expected to yield a novel sensing system which is rapid, reproducible, and suitable for automated analyzers.…”
Section: Introductionmentioning
confidence: 99%